Vaccine-Induced Antibodies Mediate Higher Antibody-Dependent Cellular Cytotoxicity After Interleukin-15 Pretreatment of Natural Killer Effector Cells - Fisher, Leigh; Zinter, Melissa; Stanfield-Oakley, Sherry; Carpp, Lindsay N.; Edwards, R. Whitney; Denny, Thomas; Moodie, Zoe; Laher, Fatima; Bekker, Linda-Gail; McElrath, M. Juliana; Gilbert, Peter B.; Corey, Lawrence; et al. (Frontiers in Immunology, 2019)
The secondary analyses for correlates of risk of infection in the RV144 HIV-1 vaccine trial implicated vaccine-induced antibody-dependent cellular cytotoxicity (ADCC) responses in the observed protection, highlighting the importance of assessing such responses in ongoing and future HIV-1 vaccine trials. However, in vitro assays that detect ADCC activity in plasma from HIV-1 infected seropositive individuals are not always effective at detecting ADCC activity in plasma from HIV-1 vaccine recipients. In vivo, ADCC-mediating antibodies must operate at the site of infection, where effector cells are recruited and activated by a local milieu of chemokines and cytokines. Based on previous findings that interleukin 15 (IL-15) secretion increases during acute HIV-1 infection and enhances NK cell-mediated cytotoxicity, we hypothesized that IL-15 pretreatment of NK effector cells could be used to improve killing of infected cells by vaccine-induced antibodies capable of mediating ADCC. Using the HIV-1 infectious molecular clone (IMC)-infected target cell assay along with plasma samples from HIV-1 vaccine recipients, we found that IL-15 treatment of NK cells improved the ability of the vaccine-induced antibodies to recruit NK cells for ADCC. Through immunophenotyping experiments, we showed that this improved killing was likely due to IL-15 mediated activation of the NK cells and higher intracellular levels of perforin and granzyme B in the IL-15 pretreated cells. We also found that using a 4-fold dilution series of plasma and subtraction of pre-vaccination responses resulted in lowest response rates among placebo recipients and significant separation between treatment groups. This represents the first attempt to utilize IL-15-treated effector cells and optimized analytical approaches to improve the detection of HIV-1 vaccine-induced ADCC responses and will inform analyses of future HIV vaccine clinical trials.